Flipped Classroom: A Good Way for Lower Secondary Physical Education Students to Learn Volleyball - Alberto Ferriz-Valero; Ove Østerlie; Salvador García-Martínez; Salvador Baena-Morales (MDPI AG, 2022)
The ubiquity of digital technology in society and school demands that teachers and students explore various pedagogical approaches to make use of those technologies in a fruitful way in order to enhance students' educational outcomes. One approach emerging in the field of physical education (PE) is the pedagogical approach called flipped classroom (FC). The first purpose of this study was to assess the effects of the application of an FC approach on 284 Spanish secondary PE students regarding learning of the conceptual content of the activity itself, in this case volleyball. The second purpose was to assess how this intervention affected their motivation from an SDT perspective. Through a quantitative approach, positive results were found regarding the positive development of autonomous motivation and cognitive learning among students following an FC approach. These results were compared to a control group following a traditional approach to PE, highlighting the relevance of the methodology applied. The findings of the present study would be valuable for policymakers and stakeholders looking to promote the integration of digital technology into PE as part of enhancing the outcomes of PE for all students and thus contributing to quality and sustainable education.